A note on the nocturnal beetle fauna of Lalang Island in the Straits of Malacca - Abdullah, Fauziah (Malaysian Journal of Science, 2008)
A total of 135 specimens were sampled, comprising of 15 species from 8 families of beetles. The species were Casnoidea sp. (Carabidae), Plandones sp. (Cerambycidae) Noserius sp. (Cerambycidae), Cheorane modesta (Chrysomelidae), Veranio discolor (Coccinellidae), Xanthopenthes sp. (Elateridae), Oxyropterus audoniwi (Elateridae), Anomala pallida (Scarabeidae), Apogonia tribicollis (Scarabeidae), Pachycorinus sp. (Staphylinidae), Amarygmus sp. (Tenebrionidae), Obriomaia sp. (Tenebrionidae) and Alphitobius diaperinus (Tenebrionidae). All species identified are 13 first records for Lalang Island. Two species from family Scarabaeidae coded as Scara 6 and Scara 8 were unidentified. Sejumlah 135 specimen yang terdiri dari 15 species dan 8 famili kumbang telah di kumpulkan. Casnoidea sp. (Carabidae), Plandones sp. (Cerambycidae), Noserius sp. (Cerambycidae), Cheorane modesta (Chrysomelidae), Veranio discolor (Coccinellidae), Xanthopenthes sp. (Elateridae), Oxyropterus audoniwi (Elateridae), Anomala pallida (Scarabeidae), Apogonia tribicollis (Scarabeidae), Pachycorinus sp. (Staphylinidae), Amarygmus sp. (Tenebrionidae), Obriomaia sp. (Tenebrionidae) and Alphitobius diaperinus (Tenebrionidae) telah ditemui. Ini merupakan tiga belas rekod baru penemuan spesies tersebut di Pulau Lalang. Dua spesies dari keluarga Scabarabeidae yang di beri kod Scara 6 dan Scara 8 tidak dapat dikenalpasti, akan dihuraikan dalam laporan lain. Implikasi penemuan ini dibincangkan.